Dietary fiber intake and mortality among survivors of liver cirrhosis: A prospective cohort study - Zahra Hariri; Azita Hekmatdoost; Fereshteh Pashayee-khamene; Sara Karimi; Salehe Ahmadzadeh; Zahra Yari (Heliyon, 2023)
Background: Liver cirrhosis is associated with significant nutritional risks and poor survival rates. Little is known about the impact of dietary factors on metabolic complications and mortality from cirrhosis. Aim: The present study investigated the potential associations between dietary fibers and the risk of cirrhosis-related mortality. Methods: In this prospective study, 121 ambulatory cirrhotic patients with more than six months of cirrhosis diagnosis were followed-up for 4 years. Dietary intakes were assessed using a 168-item semi-quantitative validated food frequency questionnaire. Crude and multivariable-adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated through cox proportional hazards regression models. Results: Comparing the highest versus the lowest tertile, soluble and insoluble fiber intake was associated with 62% (HR = 0.38, 95% CI = 0.045–3.5, p trend = 0.047) and 73% (HR = 0.27, 95% CI = 0.06–1.2, p trend = 0.021) lower mortality risk, respectively, after full adjustment for potential confounders. Higher intakes of total fiber were inversely but non-significantly associated with mortality risk. Conclusion: Comprehensive assessment of dietary fiber intake associations with cirrhosis-related mortality showed that higher intakes of soluble and insoluble fiber were significantly associated with reduced mortality risk.